1993
DOI: 10.2466/pms.1993.76.2.435
|View full text |Cite
|
Sign up to set email alerts
|

Personality Dynamics of Adolescent Boys Where the Father Was Absent

Abstract: The effects of substitute adult male role-models were examined for 60 adolescents between the ages of 13 and 18 years. Significant mean differences were found on Depression, Hypochondriasis, and Suspiciousness scales of the MMPI and Guilt and Assaultiveness of the Buss-Durkee Hostility Inventory. Interpretation of scores showed that fatherless boys who had substitute male role-models were similar in personality to boys with fathers. Adolescent boys without fathers and from lower socioeconomic families were sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Specific studies to evaluate such programs are necessary to address that question. Several evaluations of mentoring programs have been reported with mixed results regarding their effectiveness (Mech et al, 1995;Nelson & Valliant, 1993;Royce, 1998;Slicker & Palmer, 1993;Tierney et al, 1995). The natural mentoring relationships that youth form with the nonparental adults with whom they interact in their daily lives may be quite different from the relationships they form with mentors to whom they are assigned through formal programs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specific studies to evaluate such programs are necessary to address that question. Several evaluations of mentoring programs have been reported with mixed results regarding their effectiveness (Mech et al, 1995;Nelson & Valliant, 1993;Royce, 1998;Slicker & Palmer, 1993;Tierney et al, 1995). The natural mentoring relationships that youth form with the nonparental adults with whom they interact in their daily lives may be quite different from the relationships they form with mentors to whom they are assigned through formal programs.…”
Section: Discussionmentioning
confidence: 99%
“…The number of studies that examine the effects of natural mentors, however, is limited. While several researchers have provided evaluations of formal mentoring programs such as Big Brother/Big Sister (Mech et al, 1995;Nelson & Valliant, 1993;Royce, 1998;Slicker & Palmer, 1993;Tierney, Grossman, & Resch, 1995), few have explored the natural mentor relationships that some adolescents form with nonparental adults in the course of their daily lives.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, children of absent or uninvolved fathers have been shown to demonstrate evidence of maladjustment (Amato & Gilbreth, 1999;Beaty, 1995;Nelson & Valliant, 1993).…”
mentioning
confidence: 91%
“…There is currently preliminary evidence that mentored children reported reduced internalizing symptoms (Nelson & Valliant, 1993;Jackson, 2002;Keating et al, 2002). Nelson and Valliant (1993) examined depression in a group of boys without fathers who received mentoring through the Big Brothers/Big Sisters program. In this sample, they found that boys who had a Big Brother for three years were significantly less depressed than those who were either in the program without a consistent Big Brother or not in the program at all.…”
Section: Internalizing Difficultiesmentioning
confidence: 94%
“…A number of studies report no direct effects on self-esteem, self-worth, or self-concept (Nelson & Valliant, 1993;Slicker & Palmer, 1993;Tierney & Grossman, 1995;Grossman & Tierney, 1998;Royse, 1998;Rhodes et al, 2000;Keating et al, 2002). Even several large-scale studies of Big Brothers/Big Sisters participants reveal that mentoring did not significantly improve global self-worth, social acceptance, or selfconfidence (e.g.…”
Section: Sense Of Selfmentioning
confidence: 97%